Biochemical evaluation of antihyperglycemic and hypolipidemic effects of methanolic tepal extract of Musa paradisiaca studied in STZ-induced diabetic mice - Khamsah Suryati, Mohd; U.S. Mahadeva, Rao; Muhammad, Abdurrazak (2015)
The use of medicinal plants as source of remedies for the treatment of many diseases dated back to prehistory and people of all continents have this old tradition. I the present study, methanolic tepal extract (MTE) of Musa paradisiaca was evaluated for phytochemical screening, andin vivo antidiabetic therapeutic efficacy in streptozotocin (STZ)-induced diabetic mice. Diabetic mice were administered 500 mg/kg per day of MTE orally for one month. The mice were sacrificed and blood collected for key biochemical parameters such as, blood glucose, insulin, hemoglobin and glycosylated hemaoglin (HbA 1c), creatinine, urea, uric acid, total protein, lipid profile, aminotransferases and alkaline phosphatase. The histopathological studies of pancreas, liver and kidney was also performed. Preliminary phytochemical screening reveals the presence of phenolics, flavonoids, glycosides, terpenoids, tannins and alkaloids. Elevated blood glucose, HbA1c creatinine, urea and uric acid and decreased level s of plasma insulin and hemoglobin were significantly (p<0.05) reverted back to near normal in STZ-induced diabetic mice after oral administration of MTE. Plasma protein, lipid profile, transaminases and alkaline phosphatase were also significantly normalized (p<0.05) after the treatment. Histopathological analysis indicated tissue damages in the diabetic untreated mice. MTE treated groups shows the tissue protection (of pancreas and liver) against peroxidation damage, thus signifying tissue integrity maintenance of MTE. It can be inferred that thein vivo antidiabetic therapeutic efficacy of tepals of Musa paradisiaca may be attributed to the presence of phytochemicals such as phenolics, flavonoids, alkaloids etc.